FORMULASI PEMAHAMAN KARYAWAN TENTANG PENYAKIT AKIBAT KERJA DI DUNIA INDUSTRI KABUPATEN KARAWANG - Muhidin, Muhidin; Jumaedi, Jumaedi; Chaerani Tri Yuliana,; Wieke Widhiantika,; Yasin Azhari,; Wendi Darmawan, (Journal of Innovation Research and Knowledge, 2024)
This study aims to evaluate employees' understanding of occupational diseases in various industrial sectors in Karawang Regency, one of the largest industrial areas in Indonesia. Occupational diseases are a significant health issue in industrial environments, especially in high-risk sectors such as manufacturing, automotive, textile, and chemical industries. A lack of understanding among employees about the risks and prevention of occupational diseases can increase the incidence rate, reduce productivity, and raise healthcare costs for both companies and workers. This research employs a cross-sectional survey design with a quantitative approach. Data were collected from 400 employee respondents across various industrial sectors using a stratified random sampling technique to ensure sample representativeness. A structured questionnaire was used to measure employees' understanding of the types of occupational diseases, risk factors, and occupational health and safety practices (OHS). Data analysis was conducted using descriptive statistics to illustrate the distribution of employee understanding and inferential statistics such as Chi-Square tests and logistic regression to identify factors influencing employees' comprehension. The results show that only 25% of employees have a high understanding of occupational diseases, while 45% have a moderate understanding, and 30% have a low understanding. Analysis by industrial sector shows that the manufacturing sector has the highest level of understanding (35%), followed by automotive (30%), textile (20%), and chemical (15%). These findings indicate a significant gap in employee understanding across various industrial sectors, which requires more specific and intensive OHS training and education approaches. This study concludes that to improve employees' understanding of occupational diseases, companies need to adopt more targeted, interactive, and evidence-based training strategies. Additionally, collaboration between companies and local government in designing effective OHS policies is essential to ensure optimal occupational health and safety. The implications of this study provide significant contributions to national occupational health policy and can serve as a reference for further research in similar contexts